Ekspektasi Dinamika Kesejahteraan Petani di Tengah Gejolak Harga Pangan dan Inflasi pada Provinsi Jawa Timur - Zaman, Moh. Hairus; Wahyuningsih, Diah; Nugroho, R. Y. Yudo (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2025)
The purpose of this study is to estimate the future condition of the farmer exchange rate, aggregate food prices, and inflation rates and analyze the response of farmer welfare through the farmer exchange rate (NTP) to price fluctuations in food commodities such as rice, chicken meat, beef, shallots, garlic, cayenne pepper, cooking oil, sugar and eggs. The research method uses Impulse Response Function analysis and Dynamic Forecasting on the Bayesian Vector Autoregressive (BVAR) model method using secondary time series data for the period May 2017 - December 2023. The results of the variation in the response of the farmer exchange rate to each specific food price fluctuation to facilitate the identification of the type of food commodity prices that are strongly responded by the farmer exchange rate. In addition, the results of the projection of the level of farmer welfare and aggregate food prices in the next few months tend to decline amid the projected inflation rate that is still stable. This study produces several recommendations that can be used as considerations for formulating policies in maintaining the stability of food commodity prices and inflation rates to improve the welfare of farmers in East Java Province Tujuan penelitian ini untuk melakukan estimasi kondisi masa depan nilai tukar petani, harga pangan agregat, dan tingkat inflasi serta menganalisa respon kesejahteraan petani melalui nilai tukar petani (NTP) pada gejolak harga pada komoditas pangan seperti, beras, daging ayamn, daging sapi, bawang merah, bawang putih, cabe rawit, minyak goreng, gula dan telor. Metode penelitian menggunakan analisa Impulse Response Function dan Dynamic Forecasting pada metode model Bayesian Vector Autoregressive (BVAR) dengan menggunakan data sekunder time series periode Mei 2017 - Desember 2023. Hasil variasi respon nilai tukar petani pada setiap gejolak harga pangan secara spesifik untuk mempermudah dalam mengidentifikasi jenis harga komoditas pangan yang direspon kuat oleh nilai tukar petani. Di samping itu, hasil proyeksi tingkat kesejahteraan petani dan harga pangan agregat dalam beberapa bulan ke depan cenderung mengalami penurunan di tengah proyeksi tingkat inflasi yang masih stabil. Penelitian ini menghasilkan beberapa rekomendasi yang dapat dijadikan sebagai pertimbangan untuk menyusun kebijakan dalam menjaga stabilitas harga komoditas pangan dan tingkat inflasi dalam rangka meningkatkan kesejahteraan petani di Provinsi Jawa Timur.